I'm referring to a book called Communication Systems by Simon Haykin, 3rd Ed.

It says that a band-pass signal \$s(t)\$ with mid-band frequency \$f_c\$ and bandwidth \$2W\$ can be represented as follows:
$$ s(t) = s_I(t)\cos(2\pi f_c t) - s_Q\sin(2\pi f_c t) $$ where \$s_I(t)\$ is the in-phase component of \$s(t)\$, and \$s_Q(t)\$ is the quadrature-phase component of \$s(t)\$. Following this, it says that the Fourier transform of \$s_I(t)\$ is related to that of \$s(t)\$ by $$ S_I(f) = \left\{\begin{matrix} S(f-f_c) + S(f+f_c), & -W\leq f\leq W \\ 0, & \text{elsewhere} \end{matrix}\right. $$ Similarly for \$s_Q(t)\$, $$ S_Q(f) = \left\{\begin{matrix} j[S(f-f_c) - S(f+f_c)], & -W\leq f\leq W \\ 0, & \text{elsewhere} \end{matrix}\right. $$

I can't understand how the relations between \$S_I(f)\$ and \$S(f)\$, and \$S_Q(f)\$ and \$S(f)\$ are being derived.


If you multiply \$s(t)\$ with \$2\cos(2\pi f_c t)\$ and with \$-2\sin(2\pi f_c t)\$, respectively (i.e. you are actually demodulating the signal), you get:

$$s(t)\cdot2\cos(2\pi f_c t)=2s_I(t)\cos^2(2\pi f_c t)-2s_Q(t)\sin(2\pi f_c t)\cos(2\pi f_c t)=\\ =s_I(t)+[s_I(t)\cos(2\cdot2\pi f_c t)-s_Q(t)\sin(2\cdot2\pi f_c t)]$$


$$-s(t)\cdot2\sin(2\pi f_c t)=-2s_I(t)\cos(2\pi f_c t)\sin(2\pi f_c t)+2s_Q(t)\sin^2(2\pi f_c t)=\\ =s_Q(t)-[s_I(t)\sin(2\cdot2\pi f_c t)+s_Q(t)\cos(2\cdot2\pi f_c t)]$$

Note that the terms in brackets are centered at twice the carrier frequency \$f_c\$. So in the band \$-W<f<W\$ (i.e. by low-pass filtering) we get

$$s(t)\cdot2\cos(2\pi f_c t)=s_I(t)\\ -s(t)\cdot2\sin(2\pi f_c t)=s_Q(t)$$

If you take the Fourier transform of these two equations you obtain the Fourier relations stated in your question.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.